New analytical method for the quantitative analysis of ornidazole in bulk as well as various dosage forms by hydrotropic solubilisation technique - K. Rajeswar Dutt; K.N.V.Rao; Juveria Tasleem; M.Uma Devi; G.Raju (International Journal of Pharmacy and Analytical Research, 2022)
A thorough literature survey of the various analyt ical methods for the quantitative estimation of Ornidazole in both bulk drug and dosage forms has revealed that very few analytical methods are available utilizing the hydrotropic solubilization technique to date. The present research paper is a descriptio n of a new analytical method developed using the principle of Hydrotropy employing very easily available chemical namely 1M Sodium benzoate solution. The method has been validated as per ICH guidelines and found to conform to ICH guidelines. In the present investigation the use of organic solvent has been avoided due to their high cost, volatility and toxicity , making the method environmental friendly. The findings revealed that the method is new, simple, safe, environmental friendly, accu rate, precise, reproducible and cost -effective. It can be successfully employed as a routine analytical procedure for the analysis of Ornidazole tablets. Hence the authors suggest that this analytical method can be adopted in the Pharmaceutical industry for the analysis of Ornidazole in bulk and various dosage forms. . Ornidazole shows its maximum absorbance at 304 nm and Beer’s law was obeyed in concentration range of 2 -5 µg/ml in presence of 1M Sodium benzoate and Molar absorptivity was computed as 0.00 65934×103 mole-1cm-1. Sandell’s sensitivity was established as 0.0167 µg/cm2/0.001 abs.unit. Optimum photometric range was established from the Ringbom’s plot. The statistical analytical parameters namely Standard deviation and Correlation coefficient were computed and found to be 1.581, 0.996.